IPad2® Use in Patients With Implantable Cardioverter Defibrillators Causes Electromagnetic Interference: The EMIT Study. Issue 2 (11th April 2014) - Kozik, Teri M.; Chien, Gianna; Connolly, Therese F.; Grewal, Gurinder S.; Liang, David; Chien, Walter
Abstract : Background: Over 140 million iPads ® have been sold worldwide. The iPad2 ®, with magnets embedded in its frame and Smart Cover and 3G cellular data capability, can potentially cause electromagnetic interference in implantable cardioverter defibrillators. This can lead to potentially life‐threatening situations in patients. The goal of this study was to determine whether the iPad2 ® can cause electromagnetic interference in patients with implantable cardioverter defibrillators. Methods and Results: Twenty‐seven patients with implantable cardioverter defibrillators were studied. The iPad2 ® was held at reading distance and placed directly over the device with cellular data capability activated and deactivated. The manufacturers/models of devices and the patients' body mass index were noted. The presence of electromagnetic interference was detected by using a programmer supplied by each manufacturer. Magnet mode with suspension of anti‐tachycardia therapy was triggered in 9 (33%) patients. All occurred when the iPad2 ® was placed directly over the device. The cellular data status did not cause interference and no noise or oversensing was noted. There was no significant difference between the mean body mass index of the groups with or without interference. Conclusions: The iPad2 ® can trigger magnet mode in implantable cardioverter defibrillators when laid directly over the device. This is potentially dangerous if patients should develop life‐threatening arrhythmias at the same time. As new electronic products that use magnets are produced, the potential risk to patients with implantable defibrillators needs to be addressed.